Ethnic-Specific Sociodemographic Factors as Determinants of Cognitive Performance: Cross-Sectional Analysis of the Malaysian Elders Longitudinal Research Study - Nur Fazidah, Asmuje; Sumaiyah, Mat; Myint, Phyo Kyaw; Tan, Maw Pin * (Karger Publishers, 2023)
Introduction: Despite cognitive impairment being a major health issue within the older population, limited information is available on factors associated with cognitive function among Asian ethnic groups. The objective of this study was to identify ethnic-specific sociodemographic risk factors which are associated with cognitive performance.